2011
DOI: 10.1177/0042098010388954
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Centrality and Power in the World City Network

Abstract: Centrality and power have become common foci for world city network research and frequently serve as tools for describing cities' position or status in the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
101
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 43 publications
3
101
0
6
Order By: Relevance
“…This pattern of relational network is attributed to the power status of relevant nodes, in other words, power is characterized by the dependencies of other nodes (Liu, 2009). In this regard, despite some scholars have made certain distinctions between centrality and power empirically (Neal, 2011), we propose the identical definitions of this two concepts for this research. Centrality research is a dominant research orientation in the social network Vol.…”
Section: Centrality Analysismentioning
confidence: 99%
“…This pattern of relational network is attributed to the power status of relevant nodes, in other words, power is characterized by the dependencies of other nodes (Liu, 2009). In this regard, despite some scholars have made certain distinctions between centrality and power empirically (Neal, 2011), we propose the identical definitions of this two concepts for this research. Centrality research is a dominant research orientation in the social network Vol.…”
Section: Centrality Analysismentioning
confidence: 99%
“…As sketched in Figure 2, neither centrality nor power converts into each other [22]. Guangdong, for example, has a high ranking of centrality, signifying a large amount of linkages in the production chain of KIBS.…”
Section: Centrality and Powermentioning
confidence: 99%
“…Therefore, it is found that a city node with large centrality does not mean that it may own a large power in the meantime, and vice versa. In appreciating the asymmetry of city linkages, Neal [22] addressed a catalogue of world city based on the average of centrality and power. Likewise, China's city nodes can be classified into four groups, namely large centrality and huge power (e.g., Shanghai), large centrality and weak power (e.g., Guangdong), small centrality and huge power (e.g., Shan-xi), and small centrality and weak power (e.g., Xinjiang).…”
Section: Centrality and Powermentioning
confidence: 99%
“…The approaches commonly used to examine international publication trends and collaboration performance of a certain research field are bibliometrics and social network analysis. Recent studies have highlighted the necessity of also considering intercity collaboration to fully understand cooperative and innovative activities [18,19]. However, studies examining the relationships among these three levels of international scientific collaboration are not yet fully developed.…”
Section: Introductionmentioning
confidence: 99%